The Implications of Liver Biopsy Results in Patients with Myeloproliferative Neoplasms Being Treated with Ruxolitinib - Douglas Tremblay; Juan Putra; Alexander Vogel; Adam Winters; Ronald Hoffman; Thomas D. Schiano; Maria Isabel Fiel; John O. Mascarenhas (Case Reports in Hematology)
Ruxolitinib is increasingly being utilized for the treatment of myelofibrosis and polycythemia vera, but the potential for hepatic toxicity is poorly understood. We performed a retrospective review of hepatic damage occurring in patients with myeloproliferative neoplasms receiving ruxolitinib. Relevant histologic images of liver biopsies were reviewed by an experienced liver pathologist and reported to a multidisciplinary team including hepatology and hematology. A variety of liver pathology was observed including extramedullary hematopoiesis, obliterative portal venopathy, and drug-induced liver injury. In all cases reviewed, the liver biopsy had significant treatment implications. We conclude that hepatology referral and liver biopsy in patients receiving ruxolitinib therapy with biochemical evidence of liver injury reveals a variety of etiologies which have significant treatment impact. Clinicians should be aware of the potential causes of liver damage in this population and initiate prompt referral and liver biopsy.